2022
DOI: 10.1177/00332941221087911
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Self-Compassion in the Relationships Between the Three Forms of Perfectionism with Anger, Aggression, and Hostility

Abstract: The prevalence of aggression in adolescents is on the rise, and it could be a serious public health concern. Studies have found positive relationships between perfectionism with anger, aggression, and hostility. However, the moderating role of self-compassion in the links between perfectionism with anger, aggression, and hostility has not been studied. To better understand the relationships between the three forms of perfectionism with anger, aggression, and hostility, this study aimed to explore the moderatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…Specifically, maladaptive perfectionists have high maladaptive self‐standards and pursue high standards for self‐image in social interaction, but they are not confident that they can perfectly complete the performance expected by themselves and others. In the process of interpersonal communication, nursing students pay attention to their own negative performance and mistakes and are afraid of receiving negative feedback from others (Mohammadian et al, 2018), showing a high level of interpersonal pressure and interpersonal problems (Abdollahi et al, 2022; Wang et al, 2022) and a high level of interpersonal sensitivity. On the other hand, nursing students with high interpersonal sensitivity tend to have high neuroticism, and neurotic individuals are susceptible to feeling high relative deprivation because of their sensitive and suspicious characteristics (Xuan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, maladaptive perfectionists have high maladaptive self‐standards and pursue high standards for self‐image in social interaction, but they are not confident that they can perfectly complete the performance expected by themselves and others. In the process of interpersonal communication, nursing students pay attention to their own negative performance and mistakes and are afraid of receiving negative feedback from others (Mohammadian et al, 2018), showing a high level of interpersonal pressure and interpersonal problems (Abdollahi et al, 2022; Wang et al, 2022) and a high level of interpersonal sensitivity. On the other hand, nursing students with high interpersonal sensitivity tend to have high neuroticism, and neurotic individuals are susceptible to feeling high relative deprivation because of their sensitive and suspicious characteristics (Xuan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to the perfectionism social disconnection model, the development of perfectionism is traced to attachment problems that manifest as unsatisfied needs to be cared for, accepted and protected, which gradually develop into different forms of interpersonal sensitivity to reactions to others and/or interpersonal hostility towards others (Hewitt et al, 2020). Previous studies have shown that perfectionists focus on gaining recognition and appreciation, have a chronic fear of being criticized by important others, and are thus particularly sensitive to the stressors of interpersonal relationships (Abdollahi et al, 2022; Wang et al, 2022). Individuals with high interpersonal sensitivity tend to make negative evaluations of themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The teachers must integrate the 4C model in the teaching and ensure that the students master these 4Cs to prepare them for the future and foster their learning and innovation skills (Abdollahi et al, 2022). These are transferable skills that an individual can transfer from one task to another and from one job to another (Galabova, 2022).…”
Section: C Model Of Educationmentioning
confidence: 99%
“…Adicionalmente, el perfeccionismo puede afectar directamente las relaciones interpersonales al promover su deterioro y desgaste (Habke et al, 1999;Lago et al, 2005;Lozano et al, 2012). El estilo de interacción de estas personas suele estar caracterizado por la presencia de arrogancia, hostilidad y sensibilidad interpersonal: estos individuos pueden ser hoscos, orgullosos y agresivos en el trato con las personas (Abdollahi et al, 2022), mientras que en su fuero interno son muy sensibles a lo que dicen y hacen los demás (Hewitt et al, 2006). Esta sensibilidad interpersonal se re&eja en la desesperanza y en la ansiedad social (Goya-Arce & Polo, 2017;Roxborough et al, 2012), lo cual lleva a los perfeccionistas a interpretar dichas relaciones y sus resultados de manera distorsionada.…”
Section: Introductionunclassified